Brexit and its impact on New Zealand economy: A conceptual analysis / Saida Parvin … [et al.] - Parvin, Saida; Subramaniam, Geetha; A. Sadman, Nahian; Baptist, Victoria Shahaya (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2017)
‘Brexit’ which means exit of United Kingdom (UK) from the European Union (EU) is not only a European issue but has varied implications throughout the world, especially amongst its trading nations. This conceptual paper first discusses pros and cons of Brexit on UK and EU. This is seen in the light of Brexit impact on trade, unemployment rate and inflation rate. It further discusses some of the immediate implication Brexit might have on New Zealand, which is the EU’s third largest trading partner. The discussion is based on the impact post-Brexit may have in terms of trade, employment, GDP and the tourism sector in New Zealand.